2022
DOI: 10.1021/acs.energyfuels.2c01056
|View full text |Cite
|
Sign up to set email alerts
|

Development and Performance Evaluation of a Novel Silica Nanoparticle-Reinforced CO2-Sensitive Fracturing Fluid with High Temperature and Shear Resistance Ability

Abstract: In order to further increase the temperature and shear resistance of a conventional CO2-sensitive clean fracturing fluid, a novel silica nanoparticle-reinforced CO2-sensitive fracturing fluid system was developed. The system was prepared with the compositions of 2.0 wt % N-[3-(dimethylamino) propyl] oleamide, 1.5 wt % sodium p-toluene sulfonate (NaPts), and 0.025 wt % silica nanoparticles. The rheological properties, temperature resistance, shear resistance, sand-carrying capacity, gel-breaking property, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…It is of much importance that the addition of nanoparticles can significantly increase the viscosity of WLM fluid at high temperatures, because high temperature will cause the shortening of micelles, so as to provide more micelle end-caps to participate in the crosslinking with nanoparticles. 245,309 Silicon dioxide (SiO 2 ) 294,310 and metal oxides (magnesium oxide (MgO), 304 iron oxide (Fe 2 O 3 ), 311 zinc oxide (ZnO), 1 0 3 , 2 5 7 , 3 1 2 , 3 1 3 alumina (Al 2 O 3 ), 3 0 1 zirconia (ZrO 2 ), 314,315 and titanium oxide (TiO 2 ) 232,276 ) are commonly used nanoparticles to improve the temperature resistance for a fracturing fluid because they have higher reactivity and efficiency. 292 The interaction between nanoparticles and WLMs is affected by various parameters, including the type, size, and concentration of nanoparticles, surfactant concentration, temperature, and charge on surfactants and nanoparticles.…”
Section: Counterion Salt Effectmentioning
confidence: 99%
See 4 more Smart Citations
“…It is of much importance that the addition of nanoparticles can significantly increase the viscosity of WLM fluid at high temperatures, because high temperature will cause the shortening of micelles, so as to provide more micelle end-caps to participate in the crosslinking with nanoparticles. 245,309 Silicon dioxide (SiO 2 ) 294,310 and metal oxides (magnesium oxide (MgO), 304 iron oxide (Fe 2 O 3 ), 311 zinc oxide (ZnO), 1 0 3 , 2 5 7 , 3 1 2 , 3 1 3 alumina (Al 2 O 3 ), 3 0 1 zirconia (ZrO 2 ), 314,315 and titanium oxide (TiO 2 ) 232,276 ) are commonly used nanoparticles to improve the temperature resistance for a fracturing fluid because they have higher reactivity and efficiency. 292 The interaction between nanoparticles and WLMs is affected by various parameters, including the type, size, and concentration of nanoparticles, surfactant concentration, temperature, and charge on surfactants and nanoparticles.…”
Section: Counterion Salt Effectmentioning
confidence: 99%
“…292 Similarly, Gurluk et al 248 reported that the VES fluids (2−4 vol % amidoamine oxide surfactant + 0.072 wt % NPs) enhanced with MgO-NPs maintained a viscosity greater than 100 mPa•s for 6 h, while the solutions prepared with ZnO maintained a viscosity greater than 20 mPa•s for 6 h. The results indicated that the interaction between MgO particles and the surfactants is stronger than that between ZnO particles and the surfactants, bringing about a stronger network and an increase in viscosity. Liu et al 294 found that there are optimal surfactant concentrations, counterion salt concentrations, and nanosilica concentrations for the enhanced VES system with nanosilica. In the CTAB system, Nettesheim et al 306 and Helgeson et al 305 showed that increasing the concentration of NPs enhances the viscosity and elasticity of the solution.…”
Section: Counterion Salt Effectmentioning
confidence: 99%
See 3 more Smart Citations